Identification of a key locus, qRL8.1, associated with root length traits during seed germination under salt stress via a genome-wide association study in rice - Peiwen Zhu; Guolan Liu; Zhihao Chen; Deyan Kong; Lijun Luo; Xinqiao Yu (BMC Plant Biology)
Abstract Background Salt stress is a major abiotic constraint limiting rice (Oryza sativa L.) production worldwide, particularly in saline-affected regions. Improving salt tolerance at the seed germination stage is crucial for increasing stand establishment and yield stability, especially under direct seeding conditions. Identifying loci associated with salt-tolerant germination and characterizing key candidate genes offers valuable insights for breeding strategies. Results We evaluated the salt tolerance of 406 drought-resistant rice accessions at the germination stage under 0, 100, 150, and 200 mM NaCl conditions. Four germination-related traits—germination potential (GP), relative germination potential (RGP), root length (RL), and relative root length (RRL)—were measured. Significant phenotypic variation was observed, with GP, RGP, RL, and RRL sharply decreasing as the NaCl concentration increased. Using a genome-wide association study (GWAS) with 65,069 high-quality SNPs, we identified 27 significantly associated loci. Among these genes, 9 colocalized with known QTLs/genes, and 18 were identified as novel. The key locus qRL8.1, identified under 200 mM NaCl stress, contained multiple closely linked SNPs and strongly associated with RL and RRL. Expression analyses of candidate genes within qRL8.1 indicated that LOC_Os08g41790 (encoding a phosphatidylinositol/uridine kinase family protein) and LOC_Os08g42030 (encoding a peroxidase precursor) were both highly expressed in roots and strongly induced by salt stress. Haplotype analysis revealed that favorable alleles of these genes are associated with improved seed germination and root elongation under salt stress conditions. Several elite varieties carrying superior haplotypes of both genes were identified, providing valuable genetic resources for breeding salt-tolerant rice cultivars. Conclusions This study identified multiple loci conferring salt tolerance at the germination stage, with qRL8.1 emerging as a key locus. Two candidate genes, LOC_Os08g41790 and LOC_Os08g42030, were significantly associated with increased salt tolerance. The elite haplotypes and varieties identified here can be directly utilized in rice breeding programs. These findings increase our understanding of the genetic mechanisms underlying salt tolerance during early seedling establishment and offer new avenues for developing salt-resistant rice varieties.